Desain Visual Sebagai Strategi Branding Produk Makanan Lokal : Kasus Sempol Ayam Gadisa - Fiego Firman Shah; Faradika (CV. ITTC INDONESIA, 2025)
Visual communication design plays a strategic role in enhancing the competitiveness of MSMEs, particularly in the area of promotion. This community service activity was carried out to support the MSME “Sempol Ayam Gadisa” in strengthening its branding through the creation of promotional media such as banners, posters, and logos. The method used was participatory and applicative, including observation, visual design development, promotional media implementation, and evaluation. The results showed an increase in product visual appeal and sales, as well as improved awareness among business owners of the importance of visual design. The colors red, maroon, and yellow were selected for their ability to stimulate appetite and attract attention, while blue was avoided. This activity proves that visual communication design can serve as a practical and effective solution in supporting MSME product marketing directly.